OPERASI DAN ISOMORFISMA PADA GRAF FUZZY M-STRONG - Adelia Niken Puspitasari; Naimah Hijriati (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2016)
The fuzzy graph M-strong part of the fuzzy graph whose degree of membership is equal to the minimum of the two-point membership degree that links it. The aim of this research is to prove the close nature of M-strong fuzzy graph on join operation, cartesian product, composition and its complement and also to prove the isomorphism of M-strong fuzzy graph. The result of this research is that the join of two fuzzy graphs is M-strong fuzzy graph if and only if both are M-strong fuzzy graphs. Cartesian product and the composition of two M-strong fuzzy graphs will produce an M-strong fuzzy graph. If the complement of the fuzzy graph complement is the same as the fuzzy graph itself, then the fuzzy graph is the M-strong fuzzy graph. If there is an ???????? and ???????? 'isomorphic fuzzy graph then ???????? is an M-fuzzy graph if and only if ????????' is also an M-strong fuzzy graph. If fuzzy graph ???????? isomorphic co-weak with M-strong fuzzy graph ???????? 'then ???????? is also an M-strong fuzzy graph and if ???????? isomorphic with ????????' then ???????? is connected if and only if ???????? 'is also connected.